Exploring Culture in Indonesia English Textbook For Secondary Education - Qodriani, Laila Ulsi; Kardiansyah, Muhammad Yuseano (Jurnal Pendidikan Indonesia, 2018)
The curriculum in schools is always changing. There are new advancements that are being made and new components being incorporated into the curriculum. Culture and identity have become a rising issue in some schools nowadays and it has slowly begun to show its importance to the curriculum. Hence, it also has become a rich source of investigation which inseparable in the field of English Language Teaching. With this background, this study investigates the representation of culture-related contents embodied in Indonesian middle school English electronic textbook 2013 curriculum. The present study explores how culture is preserved and disseminated in the textbooks. It is descriptive qualitative in nature. The data were taken from Electronic English Textbook for VII grade entitled “When English Rings a Bell” (2014) by Kemdikbud RI, are in the form of written texts and illustrations that may accompany the reading passages. The five dimensions of culture were adopted in this study proposed by Moran (2001) which cover the products, practices, perspectives, persons and communities. The result shows that Indonesia cultural aspect chosen selectively to be included in this national textbook to enhance both teachers’ and students’ awareness for the interdependent relationship between language and culture.